2019
DOI: 10.1186/s40168-019-0703-9
|View full text |Cite
|
Sign up to set email alerts
|

NanoARG: a web service for detecting and contextualizing antimicrobial resistance genes from nanopore-derived metagenomes

Abstract: Background Direct and indirect selection pressures imposed by antibiotics and co-selective agents and horizontal gene transfer are fundamental drivers of the evolution and spread of antibiotic resistance. Therefore, effective environmental monitoring tools should ideally capture not only antibiotic resistance genes (ARGs), but also mobile genetic elements (MGEs) and indicators of co-selective forces, such as metal resistance genes (MRGs). A major challenge towards characterizing the potential huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 75 publications
(73 reference statements)
0
50
0
Order By: Relevance
“…Past work by Arumugam et al 54 has shown, in less diverse communities, that frame shift errors present in long-read assemblies can affect translation. However, recent work by Arango-Argoty et al 57 , which examined ARG detection in complex environmental samples, did not find frame shift errors to be problematic and further demonstrated that the number of ARGs detected did not increase with additional error correction. Furthermore, Canu performs a read polishing step as a part of its assembly pipeline.…”
Section: Discussionmentioning
confidence: 93%
“…Past work by Arumugam et al 54 has shown, in less diverse communities, that frame shift errors present in long-read assemblies can affect translation. However, recent work by Arango-Argoty et al 57 , which examined ARG detection in complex environmental samples, did not find frame shift errors to be problematic and further demonstrated that the number of ARGs detected did not increase with additional error correction. Furthermore, Canu performs a read polishing step as a part of its assembly pipeline.…”
Section: Discussionmentioning
confidence: 93%
“…The main advantage of long-read sequencing is the illumination of genetic context; by sequencing longer read fragments, users are not limited to simply detecting the presence of ARGs but can also identify gene clusters that show co-occurrence with other resistance genes or mobile elements that are the likely mechanisms of transfer. Specific tools have been developed for this purpose, such as the accessible web service NanoARG [64] or the interactive software MEGAN-LR [65]. These new sequencing technologies have already been used for rapid detection of ARGs, where the Oxford Nanopore MinION was successfully used in a veterinary hospital to detect ARGs, assess their taxonomy and origin, and to inform mitigation strategies [65,66].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, putatively novel resistance mechanisms were identified with deepARG (59) using a minimal sequence identity of 30% and a probability of Ͼ90% as thresholds. Additional MGEs were identified via DIAMOND blastx (-e 0.00001 -id 50 -subject-cover 50) against the MGE database of nanoARG (60). Furthermore, the MAG was screened for secondary metabolite biosynthesis clusters via antiSMASH 5.1 (61).…”
Section: Methodsmentioning
confidence: 99%